ENHANCING THE CREDIBILITY OF SUSTAINABILITY REPORTING: CHALLENGES AND OPPORTUNITIES FOR IMPLEMENTING ASSURANCE STANDARDS - Widiyati, Dian; Hendra, Lim (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
Sustainability reporting has become an important tool for companies to communicate their social, environmental, and governance performance to stakeholders. However, the reliability of the information in these reports is often questioned, so assurance standards such as AA1000AS and ISAE 3000 are used to increase credibility. This study explores the benefits, challenges, and opportunities of implementing assurance standards in sustainability reporting. An analysis of the literature shows that assurance standards increase transparency and build stakeholder trust. However, challenges such as high costs, technical complexity, and cultural barriers are barriers to effective implementation, especially for small and medium-sized companies. The study also highlights the gap between international standards and local regulations, as well as the need for harmonization to ensure relevance in various contexts. By combining in-depth interviews and analysis of sustainability reports, the study identifies strategies to address barriers, including improving internal capabilities and adapting to local expectations. These findings provide insights for companies to maximize the benefits of assurance in sustainability reporting, help them meet evolving regulatory demands and strengthen their reputation in the global market. The study contributes to the sustainability reporting literature by offering practical solutions to address implementation challenges.